2001
DOI: 10.1074/jbc.m105253200
|View full text |Cite
|
Sign up to set email alerts
|

The Angiotensin II AT2 Receptor Is an AT1Receptor Antagonist

Abstract: stimulate mainly G␣ q/11 and G␣ i/o proteins (1-5). By contrast, G-protein coupling, signaling cascades, and biological effects of AT 2 receptors are less defined. Many in vivo studies with genetic deletion or transgenic overexpression of AT 2 receptors show that the AT 2 receptor inhibits AT 1 receptor-mediated functions (6 -8). The inhibitory effect of the AT 2 receptor has often been attributed to the AT 2 -mediated activation of protein phosphatases (9). However, in several systems AT 2 receptor-mediated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
332
4
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(358 citation statements)
references
References 22 publications
17
332
4
5
Order By: Relevance
“…Further studies of investigating the difference of contractile function between maternal (adult) and fetal VSMCs would provide an answer. In addition, AbdAlla et al found AT2 receptor could bind directly to AT1 receptor in PC-12 cells and fetal fibroblasts thereby antagonize the function of the AT1 receptor [28]. Whether this accounts for the phenomenon observed in our study is not known.…”
Section: Discussionmentioning
confidence: 53%
“…Further studies of investigating the difference of contractile function between maternal (adult) and fetal VSMCs would provide an answer. In addition, AbdAlla et al found AT2 receptor could bind directly to AT1 receptor in PC-12 cells and fetal fibroblasts thereby antagonize the function of the AT1 receptor [28]. Whether this accounts for the phenomenon observed in our study is not known.…”
Section: Discussionmentioning
confidence: 53%
“…This may suggest a role for ATIP1 in AT2 receptor dimerization, a process of major importance for GPCR regulation and function (34,35). AT2 receptors have indeed been shown to heterodimerize with the AT1 subtype, and thereby inhibit the AT1 intracellular response by a novel mechanism that is independent of ligand/AT2 receptor interaction (36).…”
Section: Discussionmentioning
confidence: 96%
“…However, it has been shown that the different Ang II receptors can influence each other. [36][37][38][39][40] To exclude the possibility that the lack of one of the receptor subtypes alters the properties of the remaining receptors, we also investigated the effects of Ang-(1-7) in mice lacking all three Ang II receptor types. Although Ang-(1-7) was not able to reduce absolute MAP in the hypotensive triple KO mice, the percent changes induced by Ang-(1-7) were comparable with that in WT mice.…”
Section: Impact Ofmentioning
confidence: 99%